Youth Strike for Climate: Resistance of School Administrations, Conflicts Among Students, and Legitimacy of Autonomous Civil Disobedience—The Case of Québec - Dupuis-Déri, Francis (Frontiers in Political Science, 2021)
This text presents the results of the first research conducted on “green” actions and strikes for climate in high schools across Québec, a Canadian province that witnessed in 2019 the larger street protests of the international youth movement. Based on 20 semistructured interviews with students from 12 high schools, letters from school principals addressed to parents, and research in the media, this text reaffirms that schools are a place of political conflicts and struggles not only between students and adults but also between students in opposite currents of the movement. It is also a reminder of the involvement of young people in autonomous direct action groups (Extinction Rebellion). The discussion then focuses on potential implications of the movement for future elections, the legitimacy of these collective actions in relation to the philosophical debate about civil disobedience (John Rawls, Ronald Dworkin, Manuel Cerveza-Marzal, and Alan Carter), and the hope for a renewal of the student movement in Québec in the face of a disaster of unprecedented scale.